Cost Control Analysis with Earned Value Method in the Construction Work of Improving the Drainage Channel on the Dr. Soetomo Road, Samarinda, East Kalimantan - Atros, Pahridal; Oetomo, Wateno; Marleno, Risma (LPPM of NAROTAMA UNIVERSITY, 2025)
Dr. Soetomo Street drainage channel in Samarinda often experiences flooding during the rainy season. With the existing puddles, it will disrupt the activities of the surrounding community. If the puddle problem is not resolved, it can cause a bigger disaster that harms the local community. If the puddle problem is not resolved, it can cause a bigger disaster that harms the local community, both property and lives. Dr. Soetomo Street is one of the roads in Samarinda City that still often experiences puddles due to drainage channels that cannot accommodate or drain surface water. This research was conducted with the intention of controlling costs using the earned value method. The research method with calculations and analysis using the Earned Value Analysis Concept. The project cost performance did not match the budgeted costs in the 14th week, the costs incurred were Rp. 6,728,308,349 with an actual weight of 59.25%. The calculation of the CPI value <1 from week 1 to week 12. This means that the project from week 1 to week 14 cost more than planned or the project was more wasteful. At the end of the review period, namely week 12, the estimated total final project cost was Rp. 6,728,308,349, taken from the EAC value. If the tendency of the project performance condition is the same as at the end of the review, namely week 12, the estimated value does not exceed the project plan cost of Rp. 4,750,000,000.